The presence of hydrogenotrophic methanogens in the inoculum improves methane gas production in microbial electrolysis cells - Siegert, Michael; Li, Xiu-Fen; Yates, Matthew D.; Logan, Bruce E. (Frontiers in Microbiology, 2015)
High current densities in microbial electrolysis cells (MECs) result from the predominance of various Geobacter species on the anode. MECs inoculated from different sources often converge in terms of current production and predominance of Geobacter species despite variability in the inoculum community. Relatively less is known about the effects of inoculum source on methane gas production in MECs, and specifically whether archaeal communities similarly converge to one specific genus. MECs were examined here on the basis of maximum methane production and current density relative to the inoculum community structure. We used anaerobic digester (AD) sludge dominated by acetoclastic Methanosaeta species, and an anaerobic bog sediment where hydrogenotrophic methanogens were detected. Inoculation using solids to medium ratio of 25% w/v resulted in the highest methane production rates (0.27 mL mL–1 cm–2, gas volume normalized by liquid volume and cathode projected area) and highest peak current densities (0.5 mA cm–2) for the bog sample. Methane production was independent of solid to medium ratio when AD sludge was used as the inoculum. 16S rRNA gene community analysis using pyrosequencing and qPCR confirmed the convergence of Archaea to Methanobacterium and Methanobrevibacter, and of Bacteria to Geobacter, despite their absence in AD sludge. Combined with other studies, these findings suggest that Archaea of the hydrogenotrophic genera Methanobacterium and Methanobrevibacter are the most important microorganisms for methane production in MECs and that their presence in the inoculum improves the performance.